The main problems of labor market regulation in the region (using the example of the Komi republic) ("Journal "U". Economy. Management. Finance.", 2025)
The article is devoted to the analysis of key labor market regulation issues in the Republic of Komi. In the context of economic and social changes, the Republic of Komi faces numerous challenges, including a high unemployment rate, lack of skilled labor, and low workforce mobility. The goal of the study is to investigate the current state of the labor market in the region and identify the key problems faced by both workers and employers. The objectives include analyzing the effectiveness of existing employment programs, identifying the causes of unemployment, evaluating the quality of professional education, and proposing improvements for labor market regulation. The results show that, despite local authorities' efforts, unemployment and the lack of qualified specialists remain pressing issues. Improved interaction between employment centers, educational institutions, and employers, as well as the development of new professional training mechanisms, is required.
Keywords: labor market; unemployment; qualification; migration; employment; Komi Republic; workforce; vocational education; labor shortage; economic mobility; government regulation; social policy; demographic changes; competitiveness; regional development